Daily Care Information System Requirements: Professional Service-Driven Service Blueprint Approach - Lin, Tung-Cheng; Hwang, Lih-Lian; Dai, Hung-da; Sang, Yu-Chun (Applied Clinical Informatics, 2021)
Background Long-term care (LTC) services are a professional service-driven (PSD) system; to deliver appropriate care services to residents, health care providers first need to collect appropriate patient data and make a professional assessment. A well-designed LTC information system should therefore consider the information requirements of multidisciplinary health care providers to adequately support their care services.Objectives This study proposed a modified service blueprint—the PSD service blueprint—for visualizing interdisciplinary service providers' input and output information requirements, which correspond to their service activities.Methods The PSD service blueprint comprises five layers and seven elements. We also present a case study to illustrate the blueprint's application to daily LTC services.Results Our proposed approach could clearly illustrate the daily care activities, service providers (main actors), actors' input and output information, and suggestions for LTC information system–related applications.Conclusion The proposed PSD service blueprint can not only gather interdisciplinary LTC service providers' information system requirements but also act as a mapping tool for visualizing the care service process.
Keywords: long-term care; information system requirements; service blueprint; design thinking